METHODOLOGICAL RECOMMENDATIONS OF A SET OF HEALTH-IMPROVING EXERCISES TAKING INTO ACCOUNT THE PHYSICAL CONDITION FOR MEN AGED 60-64 YEARS (Scientific journal of the Fergana State University, 2023)
Substantiation, development and approbation at the Department of Physical Culture and Sports Activities of the Tashkent Financial Institute of the content of the development of complexes of health-improving exercises taking into account physical fitness for elderly men. The developed version of the methodology of physical education with the predominant use of exercises for physical fitness and endurance is presented. This orientation of physical exercises takes into account the negative involutional aging processes characteristic of older men, and the positive physiological effect of strength exercises on the organs and functional systems of the body, which reduce these negative processes. A method of using restorative means in the process of physical culture and wellness activities of men aged 60-64 years has been developed, including the following components: restorative means; composition of means; dose of exposure; the role of means of recovery in the system of physical culture and wellness training during the weekly cycle. The technique was developed on the basis of the specific features of the recovery effects formed using the selected recovery tools and their effect on slowing down the aging process, as well as the loading and post-loading effects resulting from strength training and endurance strength training. The effectiveness of the developed methodology has been proven.